1999
DOI: 10.1159/000019098
|View full text |Cite
|
Sign up to set email alerts
|

No Quantitative Relationship between CR1 and Lutheran Expression on Erythrocytes: In(Lu) Gene Product Is Not a Common Regulator of CR1 Expression on Erythrocytes

Abstract: The density of CR1, the C3b/C4b receptor (CD35), on erythrocytes (E) (CR1/E) is genetically determined. However, the broad distribution of CR1/E within a given genotype suggests that other genetic elements might contribute to the regulation of CR1/E. In some pathological conditions, including systemic lupus erythematosus (SLE), AIDS and hemolytic anemia, CR1 deficiency parallels the severity of the disease. When compared to healthy individuals, an accelerated decrease in CR1/E in these patients has been demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They suggested that other CR1 mutations might be important in determining copy number. Finally, in a French study of both CR1 and Lutheran system antigens, there was no weakening of Lutheran system antigens in donors with weak CR1 23 …”
Section: Discussionmentioning
confidence: 90%
“…They suggested that other CR1 mutations might be important in determining copy number. Finally, in a French study of both CR1 and Lutheran system antigens, there was no weakening of Lutheran system antigens in donors with weak CR1 23 …”
Section: Discussionmentioning
confidence: 90%
“…Moulds, unpublished data). Although it was initially reported that ln(Lu) could suppress expression of the Knops antigens 20 , however, later studies indicated that CR1 expression was not controlled by this gene 21–22 …”
Section: Localization Of the Knops Antigens To Cr1mentioning
confidence: 99%